Scene of the crime - Modiano, Patrick (b)
"Jean Bosman, now his early twenties, soon becomes aware of a set of disturbing coincidences involving an elusive woman, his childhood home, and a host of disquieting characters who seem inordinately interested in his past, for reasons he can't fathom. As he journeys into the echoes of memory, past and present become increasingly intertwined, forming a web spanning half a century"
Keywords: Memory -- Fiction